Clinical trials with interim analyses: standardizing terminology to increase clarity - Elina Asikanius; Benjamin Hofner; Lisa V. Hampson; Gernot Wassmer; Christopher Jennison; Tobias Mielke; Cornelia Ursula Kunz; Kaspar Rufibach (Trials)
Abstract Interim analyses for group-sequential decision-making are prevalent in clinical trials. Methodology is well established and has been routinely implemented over the last decades. Still, confusions and uncertainties on aspects of how to operationalize and interpret interim analyses exist for many stakeholders. In this paper, a team of statisticians from the pharmaceutical industry, academia, and regulatory agencies provide a multi-stakeholder perspective on the key concepts behind interim analyses, with the aim to introduce standard terminology to mitigate misunderstandings and facilitate clearer discussions.